γδ T Lymphocytes Coordinate Eosinophil Influx during Allergic Responses - Henriques, Maria Das Graças M.; Penido, Carmen (Frontiers in Pharmacology, 2012)
Tissue eosinophil infiltration, which is a hallmark of allergic and helminthic diseases, is mainly coordinated by T lymphocytes, via the production of eosinophilotactic chemokines. Among T lymphocyte subsets, lymphocytes expressing γδ T cell receptor have been determined as a key factor for eosinophil accumulation via direct and indirect mechanisms. This knowledge is strongly supported by the fact that, in different experimental models of eosinophilic airway inflammation and helminth-induced Th2 lung inflammation, an evident tissue accumulation of γδ T lymphocytes is observed. In addition, the depletion of γδ T lymphocytes is correlated with the impairment of eosinophil accumulation in inflamed tissue. γδ T lymphocytes are non-conventional T lymphocytes, which comprise a minor T lymphocyte subset, mainly distributed in the tissue, and present crucial roles in innate and acquired immune responses. γδ T lymphocytes recognize several danger- and pathogen-associated molecular pattern molecules and stress antigens in a MHC-independent fashion and can provide rapid tissue-specific responses, via the production of a wide range of chemical mediators capable to modulate other cell populations. These mediators include chemoattractant cytokines and chemokines that attract eosinophils into the tissue by either direct recognition (such as IL-5, CCL11/eotaxin), or indirect mechanisms via the modulation of αβ T lymphocytes and macrophages (through the production of interferon-γ, IL-4, and CCL2/Monocyte chemoattractant protein-1, MCP-1, for example). The present review presents an overview of how γδ T lymphocytes coordinate eosinophil accumulation in allergy, by focusing on their role in airway inflammation and by discussing the involvement of cytokines and chemokines in this phenomenon.